Investigation on Microstructure, Micro segregation and Mechanical Properties of ATIG welded Alloy C-276. (2018) - Manikandan, M.; Raj, A. Danny; Kumar, M. Sathish; Arivazhagan, N.; Gunachandran, R.; Kumar, J.K. Mohan; Vignesh, V.; Yoganathan, D.
Abstract: This research article reports the activated flux tungsten inert gas (ATIG) welding of alloy C-276. Microstructures of the welded joint were studied using optical and scanning electron microscope. Energy-dispersive X-ray spectroscopy (EDS) analysis showed that segregation of Mo and W lead to the formation of the secondary phases. The microstructure results show that fine cellular structure was observed in the fusion zone. Studies using scanning electron microscopy revealed the formation of secondary phases in the grain boundaries. Strength and ductility of the welded joint was evaluated using tensile test. It was inferred that the joint strength was almost matching to the strength of the base metal. It was deduced that the formation of the secondary phases had reduced the ductility and toughness of the weld joint.